Sabatier principle of metal-support interaction for design of ultrastable metal nanocatalysts - Hu, Sulei; Li, Wei-Xue (Science (American Association for the Advancement of Science), 2021)
Sintering of nanoparticles is one of the main causes of their catalytic deactivation. Rational design of nanocatalysts that are stable against sintering is a grand challenge in heterogenous catalysis. Hu et al . present kinetic theories for two competing sintering mechanisms, Ostwald ripening and particle migration, which relate the rates of both processes to fundamental interaction energies in metal nanoparticle-support combinations. Using kinetic simulations for hundreds of such pairs, the authors show a universal volcano dependence of the sintering kinetics on the metal-support binding energy that can serve as a single descriptor to predict nanoparticle growth rates. The revealed scaling relations are a good start in the development of high-throughput screening computational approaches to drive discovery of sintering-resistant nanocatalysts. —YS Scaling relations enable the high-throughput screening of supports to boost the stability of nanocatalysts against sintering. The stability of supported nanocatalysts is crucial to meeting environmental and energy challenges and necessitates fundamental theory to relieve trial-and-error experimentation and accelerate lab-to-fab translation. Here, we report a Sabatier principle of metal-support interaction for stabilizing metal nanocatalysts against sintering based on the kinetic simulations of 323 metal-support pairs using scaling relations from 1252 energetics data. Too strong of an interaction is shown to trigger Ostwald ripening, whereas too weak of an interaction stimulates particle migration and coalescence. High-throughput screening of supports enables the sintering resistance of nanocatalysts to reach the Tammann temperature on homogeneous supports and far beyond it on heteroenergetic supports. This theory, which is substantiated by first-principles neural network molecular dynamics simulations and experiments, paves the way for the design of ultrastable nanocatalysts.